Effect of solution heat treatment on the microstructure and crystallographic texture of IN939 fabricated by powder bed fusion-laser beam - Merve Nur Doğu; Seren Ozer; Mustafa Alp Yalçın; Kemal Davut; Güney Mert Bilgin; Muhannad Ahmed Obeidi; Håkan Brodin; Hengfeng Gu; Dermot Brabazon (Journal of Materials Research and Technology, 2023)
The effect of various solution heat treatment temperatures (i.e., 1120, 1160, 1200 and 1240 °C) on the microstructure, grain morphology and crystallographic texture of IN939 fabricated by powder bed fusion-laser beam (PBF-LB) was investigated. Microstructural analyses showed that the high-temperature gradient and rapid solidification of the PBF-LB processing caused different resulting microstructures compared to conventionally produced counterparts. The melt pool morphologies and laser scanning paths were examined in the as-fabricated samples in the XZ- and XY-planes, respectively. After the application of solution heat treatment at 1120 °C, the as-fabricated PBF-LB initial microstructure was still apparent. For solution heat treatments of 1200 °C and above, the melt pool and scanning path morphologies disappeared and converted into a mixture of columnar grains in the XZ-plane and equiaxed grains in the XY-plane. On the other hand, large equiaxed grains were observed when the samples were solutionized at 1240 °C. Additionally, γ′ phase precipitated within the matrix after all solution heat treatment conditions, which led to increase in the microhardness values. According to electron backscatter diffraction (EBSD) analyses, both as-fabricated and solution heat-treated samples had intense texture with {001} plane normal parallel to the building direction. The first recrystallized grains began to appear when the samples were subjected to the solution heat treatment at 1160 °C and the fraction of the recrystallized grains increased with increasing temperature, as supported by kernel average misorientation (KAM) and grain spread orientation (GOS) analyses.